Valorization of poultry slaughterhouse sludge oil: a strategy to reduce Brazil's dependency on soybean oil in the biodiesel industry. Issue 14 (20th June 2022) - Kunh, Sheila Simone; Kugelmeier, Cristie Luis; Mantovan, Fabiana de Marqui; Lenz, Guilherme Felipe; Sattolo, Natalia Meinl Schmiedt; Milinsk, Maria Cristina; Alves, Helton José
ABSTRACT: During the poultry industrialization process the so-called sludge oil, a residual chicken fat, is recovered in the wastewater treatment plant and its use presents potential as raw material for biodiesel production. Thus, the aim of the study was to prepare blends of sludge oil with soybean oil to obtain fatty acid methyl esters (FAME) through the homogeneous alkaline transesterification reaction. To perform this study, a simple pre-treatment process – heating and subsequent filtration – was used, allowing sludge oil to be mixed with soybean oil to compose blends, without the need to use more sophisticated pre-treatment processes. After this step, blends ranging from 5% to 90% (m/m) of sludge oil mixed with soybean oil were prepared. The results showed that the molar ratio (1:6 oil blend:methanol), catalyst concentration 0.5% NaOH (mcat /moil ), at 65 °C for 60 min yielded FAME above 99.0 and 90.0% (m/m) for blends with up to 5 and 15% sludge oil, respectively. By increasing the temperature to 70 °C, under the same selected parameters, the blend with 10% sludge oil provided yield above 99.0% (m/m), presenting appropriate physicochemical properties, within the parameters required by National Agency of Petroleum, Natural Gas and Biofuels (ANP). These findings show the great potential sludge oil provides to reduce Brazil's dependency on soybean oil for biodiesel production. Highlights Sludge oil, a waste raw material for biodiesel production, is not yet explored in Brazil. A procedure for biodiesel production using soybean oil and sludge oil blends was proposed. The best reaction condition was 1:6 oil blend:MeOH molar ratio; 0.5% NaOH (mcat /moil ), at 70 °C for 60 min. Biodiesel yield was higher than 99% (m/m) under optimal reaction conditions. Sludge oil represents a promising waste raw material for biodiesel production. GRAPHICAL ABSTRACT: UF0001